Norforce: Major General Edward Northey and the Nyasaland and North-Eastern Rhodesia Frontier Force, January 1916 to June 1918 - Anderson, Ross (Scientia Militaria - South African Journal of Military Studies, 2016)
The campaign in East and Central Africa during the First World War has received relatively little attention despite the remarkable exploits of Major General Edward Northey and Norforce. In field command for two and a half years, he successfully led a multi-ethnic and polyglot force across some of the most difficult terrain of the war. Exerting strong leadership and overseeing detailed logistical planning, Northey was able to maintain an effective force that was consistently able to march and fight the German Schutztruppe under von Lettow-Vorbeck. In contrast to the main body of the British East African Force, Norforce maintained its combat effectiveness despite high levels of sickness and highly trying climatic conditions. Overall, Northey must be considered the outstanding British general of the East African Campaign while Norforce deserves full credit for its singular achievements.